2019
DOI: 10.1002/fee.2112
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic noise in US national parks – sources and spatial extent

Abstract: In an era of unprecedented environmental change, US national parks are refuges of natural ecosystems and facilitate connections between humans and nature. However, anthropogenic noise is an increasingly pervasive threat in these parks. To diagnose noise levels and sources, we analyzed thousands of hours of acoustic recordings collected across park units and summarized results from continental‐scale sound models. We found that anthropogenic noise was audible in 37% of park recordings, and that parks with high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Unintended noise from aircraft traffic is one of the most pervasive anthropogenic sounds in US National Park units (Buxton et al . 2019). Despite the ubiquity of aircraft, little assessment of its ecological impacts has been attempted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unintended noise from aircraft traffic is one of the most pervasive anthropogenic sounds in US National Park units (Buxton et al . 2019). Despite the ubiquity of aircraft, little assessment of its ecological impacts has been attempted.…”
Section: Discussionmentioning
confidence: 99%
“…(2011) and Buxton et al . (2019). Briefly, the NSNSD has been monitoring the acoustic environment at sites across the park system since 2000 (National Park Service 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noise pollution from anthropogenic sources, including road traffic, airplanes, landscaping services, and construction, pose threats to the well-being of humans and wildlife, especially around urban areas, where noise pollution tends to be greatest [2]. Noise pollution is also surprisingly common in protected areas, national parks, and rural areas, where it similarly affects both humans and wildlife [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic noise in national parks worldwide has been identified as a growing issue of concern [1][2][3]. In the US a recent noise survey across 251 sites in 66 parks indicated that such noise was audible in 37% of recordings [4]. In New Zealand the Department of Conservation (DoC) has noted increases in the numbers of domestic and international park visitors that has resulted in a corresponding demand for their diverse expectations to be catered for [5].…”
Section: Introductionmentioning
confidence: 99%